Somatotype components as useful predictors of disordered eating attitudes in young female ballet dance students - Alvero-Cruz, José Ramón; Parent-Mathias, Verónica; García-Romero, Jerónimo (MDPI, 2020)
The current study used receiver operating characteristic (ROC) curve analysis to examine the accuracy of somatotype components in correctly classifying disordered eating attitudes (DEA) in female dance students. Participants were a sample of 81 female dancers distributed in two groups: beginner training (BT; age (mean ± SD) = 10.09 ± 1.2 years, n = 32) and advanced training (AT; age = 15.37 ± 2.1 years, n = 49). For evaluation of DEA, the Eating Attitudes Test-26 (EAT-26) questionnaire was used. We defined an EAT-26 score ≥20 as positive for DEA. Somatotype components were calculated using the Heath-Carter anthropometric method. The risk of presenting DEA was 28.1% (n = 9) in the BT group and 6.1% (n = 3) in the AT group. In the BT group, mesomorphy demonstrated moderate–high accuracy in predicting DEA (area under the curve (AUC) = 0.82, 95% confidence interval (CI): 0.64–0.93). The optimal cut-off of 6.34 yielded a sensitivity of 0.77 and a specificity of 0.95. Ectomorphy showed moderate accuracy in predicting DEA (AUC = 0.768, 95% CI: 0.58–0.89). The optimal cut-off of 2.41 yielded a sensitivity of 0.78 and a specificity of 0.78. In the AT group, none of the components demonstrated accuracy in predicting DEA. Somatotype components were good predictors of disordered eating attitudes in the younger dance student group (beginner training). Further research is needed to identify the determinants of these differences between the two groups. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Conducta alimentaria - Trastornos; Bailarines - Alimentación; Dance students; Disordered eating attitudes; Eating Attitudes Test-26 (EAT-26); Ectomorphy; Mesomorphy; Receiver Operating Characteristics (ROC) curve analysis